Evaluation of cell-penetrating peptides as tools to improve nose-brain delivery of insulin - Brown, Alexander (2024)
Changes in brain insulin signalling are implicated in many neurodegenerative and psychiatric disorders, including Alzheimer’s disease (AD). There is therefore great interest in the therapeutic value of insulin-based therapies that have potential to overcome cognitive and emotional deficits. However, efficient delivery of large molecules, to the brain is hampered by the blood-brain barrier (BBB). Nasal administration represents an opportunity to bypass the BBB and exploit direct olfactory and trigeminal nerve nose-to-brain delivery routes. But uptake is relatively inefficient, so as little as 0.5% of an administered dose reaches its intended target. This MRes thesis involved in vitro studies to assess the ability of a novel cell-penetrating peptide (CPP) delivery system, termed the glycosaminoglycan (GAG)-binding enhanced transduction (GET)system, to enhance insulin delivery. Insulin-GET nanocomplexes (NCs) can be generated via electrostatic interaction. Application of these NCs to cultured RPMI 2650 nasal epithelial cells increased insulin uptake by as much as 10.5-fold compared to insulin alone without affecting cell viability. In a transwell permeation assay, insulin-GET NCs demonstrated a 12-fold increase in apical to basal accumulation compared to insulin alone, without affecting barrier integrity or metabolic activity. These encouraging in vitro findings support the further evaluation of whether GET can improve delivery of insulin to the brain in vivo. This is more complex than the in vitro setting as it requires perineuronal and/or perivascular transport after epithelial penetration.